2008
DOI: 10.1057/jibs.2008.84
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal influence as an alternative channel communication behavior in emerging markets: The case of China

Abstract: Channel communications in emerging markets are embedded in the intricacy of economic and sociocultural environments. Managing channel relationships in emerging markets therefore requires more than formal interfirm communication to rely on interpersonal influence. Extending embeddedness theory, we offer a conceptualization incorporating three embedding elements – task environment, social relations, and institutional norms – into a preliminary model that specifies the antecedents, moderators, and contingent cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
151
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(154 citation statements)
references
References 66 publications
3
151
0
Order By: Relevance
“…Task and emotional conflict are chosen as the focal variables in this paper, considering their high occurrence and renowned impact in Sino-US business relationships (Su, Yang, Zhou, Zhuang, & Dou, 2009;Wong & Tjosvold, 2010;Zhuang, Xi, & Tsang, 2010). Furthermore, length of business relationships and length of employment are hypothesised as moderators of the GRX conflict management framework.…”
Section: Introductionmentioning
confidence: 99%
“…Task and emotional conflict are chosen as the focal variables in this paper, considering their high occurrence and renowned impact in Sino-US business relationships (Su, Yang, Zhou, Zhuang, & Dou, 2009;Wong & Tjosvold, 2010;Zhuang, Xi, & Tsang, 2010). Furthermore, length of business relationships and length of employment are hypothesised as moderators of the GRX conflict management framework.…”
Section: Introductionmentioning
confidence: 99%
“…Following the research of Su et al (2009), these items assessed key features of guanxi practice in China business environment. On this basis, we conceptualize and measure guanxi orientation congruence between manufacturers and distributors in terms of objective fit, which assumes that manufacturer and distributor guanxi orientation values exist independently (Edwards and Cable, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we collect qualified 342 dyads of questionnaire, with a response rate of 55.8%. The methodological design for collecting dyadic data not only diversifies our data and research perspectives, but also provides our study with advantage of reducing common method variance associated with unilateral data, checking data quality, and observing firm behavior differences and perception bias across various dimensions (Su et al, 2009;Huang et al, 2016). To test nonresponse bias, we compared firm attributes (size, revenues, and relationship length) of respondent distributors and non-respondent firms.…”
Section: Data and Samplementioning
confidence: 99%
“…The strategic orientations of firms represent the elements of the firm's culture that guide interactions in the marketplace and impact managerial decision making (Noble et al, 2002). Guided by guanxi orientation, the extent to which boundary spanners use interpersonal guanxi is determined by their firms' strategic needs and their cultural norms simultaneously (Luo, 2001;Su et al, 2009). Murray and Fu (2016) pointed out that, as business exchanges are embedded in social relationships and guanxi permeates throughout the Chinese society allround, examining how firms employ guanxi as a strategic orientation is of high significance.…”
Section: Guanxi Orientationmentioning
confidence: 99%
“…Previous research has suggested that termination of interpersonal relationship formed between boundary spanners from buyer and seller firms has damaging effects on inter-organizational relationship (Su et al, 2009;*Corresponding author. E-mail: panx3.14@sem.tsinghua.edu.cn.…”
Section: Introductionmentioning
confidence: 99%